Advantages and challenges of self-assembled monolayer as a hole-selective contact for perovskite solar cells. (8th March 2023) - Wang, Songran; Guo, Huanxin; Wu, Yongzhen
Abstract: Charge-transporting layers (CTLs) are important in determining the performance and stability of perovskite solar cells (PSCs). Recently, there has been considerable use of self-assembled monolayers (SAMs) as charge-selective contacts, especially for hole-selective SAMs in inverted PSCs as well as perovskite involving tandem solar cells. The SAM-based charge-selective contact shows many advantages over traditional thin-film organic/inorganic CTLs, including reduced cost, low optical and electric loss, conformal coating on a rough substrate, simple deposition on a large-area substrate and easy modulation of energy levels, molecular dipoles and surface properties. The incorporation of various hole-selective SAMs has resulted in high-efficiency single junction and tandem solar cells. This topical review summarizes both the advantages and challenges of SAM-based charge-selective contacts, and discusses the potential direction for future studies.